Ethnopharmacy of Selected Medicinal Plants in a Group of Infants of Educated and Employed Mothers in Amman City - A. Al-Zeidaneen, Safaa (International Journal of Child Health and Nutrition, 2017)
Background: Employed mothers have little time for infant care and doctor visit. They resemble other women who prefer using medicinal plants to treat minor and self-limited medical problems. Objective: To investigate the frequency of using selected medicinal plant among infants of educated and employed mothers and the indications of use for these medicinal plants in Jordan. Methods: Observational study was conducted on employed mothers of 100 infants (50 males; 50 females) aged between 2-12 months in Jordan. Infants were divided according to gender into males and females and they were further subdivided into < 6 months and ≥6 months according to age. Infants' mothers were interviewed and asked about the usage and indications of the selected medicinal plants. The health and socio-demographic data were collected by the principal investigator through a valid and reliable questionnaire. Results: Employed mothers frequently used medicinal plants to treat infantile colic, constipation, coughing or inability to sleep. The most frequently used medicinal plant among employed mothers was anise, Pimpinella anisum (44%) especially for infants aged <6 months which was negatively correlated with infantile colic and positively correlated with induce sleep indication. Thymus vulgaris was commonly used to treat cough (40%) followed by both chamomile, Matricaria aurea and anise, Pimpinella anisum (30%) while, sage, Salvia triloba was the most frequently used medicinal plants to treat infantile colic (35.71%). Conclusion: Employed and well-educated mothers frequently used medicinal plants among their infants. The safety of using medicinal plants among infants is questionable.